1997
DOI: 10.1111/1467-9485.00071
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth, Participation and Communication

Abstract: The issue of communication between workers and firms has become important in recent political and economic policy debates. The most obvious example of this is the debate over whether the UK should adopt the Social Chapter of the Maastricht Treaty, which would make it mandatory for many firms to consult and communicate with their workforce. Another example is the debate over whether workers should be regarded as ‘stakeholders’. In this paper we use establishment level data from the 1990 WERS survey to show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Gist, Stevens and Baveta (1991) found that many complex tasks in organizations require job skills which include communication, teamwork, problem solving, initiative, planning, learning and technology use, they further established that direct confrontation, and conflict resolution, can be solved by applying knowledge and skills gained from prior related work experience. Furthermore, Kersley et al (1997) highlights that most employees fail because of inadequate job skills, and the inability to communicate with colleagues. Rastogi (2000) found a link between job skills and better organizational performance, higher productivity and profitability.…”
Section: Job Skills and Organizational Performancementioning
confidence: 99%
“…Gist, Stevens and Baveta (1991) found that many complex tasks in organizations require job skills which include communication, teamwork, problem solving, initiative, planning, learning and technology use, they further established that direct confrontation, and conflict resolution, can be solved by applying knowledge and skills gained from prior related work experience. Furthermore, Kersley et al (1997) highlights that most employees fail because of inadequate job skills, and the inability to communicate with colleagues. Rastogi (2000) found a link between job skills and better organizational performance, higher productivity and profitability.…”
Section: Job Skills and Organizational Performancementioning
confidence: 99%
“…S. 218f). Empirische Befunde zur industriellen Arbeitsorganisation deuten an, dass Produktivitätszuwächse in jenen Betrieben am nachhaltigsten ausgeprägt sind, die ihren Arbeitskräften Raum zur Partizipation sowie zur informellen Kommunikation einräumten (Kersley / Martin 1997). Entsprechend fungieren das Ausbildungsniveau und die Lernfähigkeit der Arbeitskräfte als Determinanten internationaler Wettbewerbsfähigkeit (Reich 1991).…”
Section: Innovationssysteme Und Regionalentwicklungunclassified
“…Most studies on individual practices have looked at human resource management (HRM). Significant improvements in firm performance have been found with more employee training (de Grip and Sieben, 2005; Dearden et al, 2006), better communication between employees and management (Kersley and Martin, 1997;Bartel, 2004), greater employee participation in decision making (Black and Lynch, 2004;Srivastava et al, 2006), and performance-related pay and promotion (Kahn and Sherer, 1990;Audas et al, 2004). Performance pay is a particularly powerful practice, as shown by Bandiera et al (2007) who found a 21% increase in workers' productivity in response to the introduction of managerial performance pay (see also Lazear (2000) who found a 44% productivity increase following a shift from flat to piece wage rate.)…”
mentioning
confidence: 99%